Accuracy of 30‐Day Recall for Components of Sexual Function and the Moderating Effects of Gender and Mood. (26th June 2013) - Weinfurt, Kevin P.; Lin, Li; Dombeck, Carrie B.; Broderick, Joan E.; Snyder, Denise C.; Williams, Megan S.; Fawzy, Maria R.; Flynn, Kathryn E.
Abstract Introduction Despite the ubiquity of 1‐month recall periods for measures of sexual function, there is limited evidence for how well recalled responses correspond to individuals' actual daily experiences. Aim To characterize the correspondence between daily sexual experiences and 1‐month recall of those experiences. Methods Following a baseline assessment of sexual functioning, health, and demographic characteristics, 202 adults from the general population (101 women, 101 men) were recruited to complete daily assessments of their sexual function online for 30 days and a single recall measure of sexual function at day 30. Main Outcome Measures At the baseline and 30‐day follow‐ups, participants answered items asking about sexual satisfaction, sexual activities, interest, interfering factors, orgasm, sexual functioning, and use of therapeutic aids during the previous 30 days. Participants also completed a measure of positive and negative affect at follow‐up. The main outcome measures were agreement between the daily and 1‐month recall versions of the sexual function items. Results Accuracy of recall varied depending on the item and on the gender and mood of the respondent. Recall was better (low bias and higher correlations) for sexual activities, vaginal discomfort, erectile function, and more frequently used therapeutic aids. Recall was poorer for interest, affectionate behaviors (e.g., kissing), and orgasm‐related items. Men more than women overestimated frequency of interest and masturbation. Concurrent mood was related to over‐ or underreporting for six items addressing the frequency of masturbation and vaginal intercourse, erectile function, and orgasm. Conclusions A 1‐month recall period seems acceptable for many aspects of sexual function in this population, but recall for some items was poor. Researchers should be aware that concurrent mood can have a powerful biasing effect on reports of sexual function. Weinfurt KP, Lin L, Dombeck CB, Broderick JE, Snyder DC, Williams MS, Fawzy MR, and Flynn KE. Accuracy of 30‐day recall for components of sexual function and the moderating effects of gender and mood. J Sex Med 2014;11:678–696.